2015
DOI: 10.1002/mus.24469
|View full text |Cite
|
Sign up to set email alerts
|

Task and intensity alters the rms proportionality ratio in the triceps surae

Abstract: Task and intensity influences the ratio of activation in the triceps surae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The reason for this difference may be due to the differential contributions of the LG and MG to isometric peak force production. 26 However, the MG was found to be the greatest contributor to triceps surae activation during maximal voluntary isometrics contractions 26 and so one might have expected MG architecture to have demonstrated a higher association to IMTP peak force capacity in the present study. The fact that MG muscle thickness and pennation angle was recently reported to be correlated with 1-RM power clean performance (ρ = 0.48-0.54, p < 0.05), 6 a task which is highly related to IMTP peak force (r = 0.74, p ≤ 0.05), 16 emphasises this notion.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The reason for this difference may be due to the differential contributions of the LG and MG to isometric peak force production. 26 However, the MG was found to be the greatest contributor to triceps surae activation during maximal voluntary isometrics contractions 26 and so one might have expected MG architecture to have demonstrated a higher association to IMTP peak force capacity in the present study. The fact that MG muscle thickness and pennation angle was recently reported to be correlated with 1-RM power clean performance (ρ = 0.48-0.54, p < 0.05), 6 a task which is highly related to IMTP peak force (r = 0.74, p ≤ 0.05), 16 emphasises this notion.…”
Section: Discussionmentioning
confidence: 55%
“…Although the associations of IMTP peak force with both VL and LG muscle structure have been recently explored in elite and junior surfers 3,12 , this population represent a very specific athletic group and thus the relationships noted may lack transferability. Furthermore, medial gastrocnemius (MG) muscle activation was recently reported to be around 10.5% greater than LG activation across various dynamic and isometric tasks 26 and so establishing relationships between MG muscle structure and IMTP peak force may be of greater interest to practitioners. The aims of the present study were, therefore, to explore whether aspects of VL and MG muscle structure were related to the IMTP peak force capacity of collegiate athletes from a variety of sports.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, recent studies have demonstrated significant correlations between distinct aspects of lateral gastrocnemius (LG) muscle architecture and athletic performance [ 3 , 4 ]. Medial gastrocnemius (MG) activation was, however, recently reported to be 4.0% and 10.5% greater than soleus and LG activation, respectively, across a range of dynamic and isometric tasks [ 5 ]. The aforementioned results suggest that the MG contributes to athletic performance to a greater extent than the other triceps surae muscles and thus MG architectural properties may also demonstrate stronger relationships to performance tasks and elicit greater training adaptations in comparison to soleus and LG.…”
Section: Introductionmentioning
confidence: 99%
“…), as part of a centrally derived recruitment strategy to sustain force when VL contraction is impaired. This is further supported by work on the planter flexors which demonstrated different extents of synergistic compensation over various types of exercises (Ball and Scurr ). To establish this, further study is needed to measure the other quadriceps muscles following EO such as the rectus femoris and vastus medialis.…”
Section: Discussionmentioning
confidence: 72%